Kebijakan Pemerintah Indonesia dalam menanggulangi Pengaruh Inflasi Terhadap Daya Beli Masyarakat - Maulana, Ilham; Haikel, Muhammad Husain; Irfan, Muhammad Nadirul; Hafid, Cep Abdul; Rafie, Muhammad Hafiz Ahza; Ginanjar, Agim; Musaffa, Farhan; Herdiana, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
High inflation can significantly pressure people's purchasing power as rising prices of goods and services reduce consumers' ability to meet daily needs. This study aims to analyze the Indonesian government's policies in mitigating the impact of inflation on purchasing power. The method used is library research by analyzing various literature and journals related to inflation, purchasing power, and macroeconomic policy in Indonesia. The results show that the government, through monetary and fiscal policies such as interest rate control, subsidies, and regulation of staple goods prices, plays a key role in maintaining price stability and purchasing power. Controlled inflation allows for balanced economic growth and supports public welfare. However, challenges remain in implementing these policies to ensure that the impact of inflation does not overly burden low-income groups.